Penerapan Fisioterapi Dada Efektif Untuk Bersihan Jalan Nafas Pada Anak Usia 6-12 Tahun - Nahari Taufika Qomsa; Norman Wijaya Gati (Jurnal Medika Nusantara, 2023)
Background: The age of children who have infections in the respiratory tract causes excess secret production. With this condition causing the patient to experience shortness of breath, so as not to get to complications, treatment is needed, one of which is removing phlegm by means of chest physiotherapy. Objective: This study was to determine the effect of chest physiotherapy on airway clearance. Methods: This study used 2 child respondents who were conducted from 21-25 August 2023 in Dayu Hamlet RT 02 RW 03 Tawang Village, Weru District, Sukoharjo Regency with each respondent being given an intervention for 5 consecutive days with the type of One Group Pretest Post test design. Results : Statistics obtained respiration rate before chest physiotherapy was carried out with the 1st respondent, namely 38 to 25 and the 2nd respondent, namely 35 to 28, which means that there is an effect of chest physiotherapy on a decrease in respiratory frequency and there is no intercostal retraction in the two respondents, which means there is a difference in the results airway clearance before and after chest physiotherapy. Conclusions : After chest physiotherapy can be useful for removing phlegm in children who are experiencing ineffective airway clearance